On Faster Integer Calculations using Non-Arithmetic Primitives - Lürwer-Brüggemeier, Katharina; Ziegler, Martin (arXiv:0709.0624)
The unit cost model is both convenient and largely realistic for describing integer decision algorithms over (+,*). Additional operations like division with remainder or bitwise conjunction, although equally supported by computing hardware, may lead to a considerable drop in complexity. We show a variety of concrete problems to benefit from such NON-arithmetic primitives by presenting and analyzing corresponding fast algorithms.

Real Computability and Hypercomputation - Ziegler, Martin

Interactive Refinement of a Material Flow Simulation Model by Comparing Multiple Simulation Runs in one 3D Environment - Fischer, Matthias; Laroque, Christoph; Huber, Daniel; Krokowski, Jens; Mueck, Bengt; Kortenjan, Michael; Aufenanger, Mark; Dangelmaier, Wilhelm (European Simulation and Modelling Conference (ESM 2007))
The validation of material flow models as well as the selection of promising strategies for the generation of a successful experiment plan is a time-consuming process. A new approach is presented, which supports the simulation expert in his working process by giving him the opportunity to modify the simulated simulation run and afterwards compare the effects of his modification with the original setting, online and in one user interface, implemented by switching the visualizations between the simulation runs or opening up to 5 parallel 3D windows. The method developed therefore clones existing simulation runs online and allows the navigation within these existing simulation runs. The method has been implemented and is validated by a test model, which describes in detail the new working process of a modeler. New research questions are derived from this work, which will define following working steps.

Ein ganzheitlicher Ansatz zur immersiven 3D-Materialflusssimulation innerhalb der Digitalen Fabrik - Dangelmaier, Wilhelm; Laroque, Christoph; Fischer, Matthias (Augmented & Virtual Reality in der Produktentstehung)

Multiple-Access Relay Channel with Network Coding and Non-Ideal Source-Relay Channels - Woldegebreal, Dereje H.; Karl, Holger (2007 4th International Symposium on Wireless Communication Systems)

Optimizing sleeping intervals in preamble sampling MAC for WSNs - Karl, Holger

Estimating Clustering Indexes in Data Streams - Buriol, Luciana S.; Frahling, Gereon; Leonardi, Stefano; Sohler, Christian (Proceedings of the 15th European Symposium on Algorithms (ESA))
We present random sampling algorithms that with probability at least 1 − δ compute a (1 ±ε)-approximation of the clustering coefficient and of the number of bipartite clique subgraphs of a graph given as an incidence stream of edges. The space used by our algorithm to estimate the clustering coefficient is inversely related to the clustering coefficient of the network itself. The space used by our algorithm to compute the number K 3,3 of bipartite cliques is proportional to the ratio between the number of K 1,3 and K 3,3 in the graph. Since the space complexity depends only on the structure of the input graph and not on the number of nodes, our algorithms scale very well with increasing graph size. Therefore they provide a basic tool to analyze the structure of dense clusters in large graphs and have many applications in the discovery of web communities, the analysis of the structure of large social networks and the probing of frequent patterns in large graphs. We implemented both algorithms and evaluated their performance on networks from different application domains and of different size; The largest instance is a webgraph consisting of more than 135 million nodes and 1 billion edges. Both algorithms compute accurate results in reasonable time on the tested instances.

Interaction of radiation with matter. Part II: Light and electrons - Schindlmayr, Arno (Probing the Nanoworld)

Time-dependent density-functional theory for extended systems - Botti, Silvana; Schindlmayr, Arno; Del Sole, Rodolfo; Reining, Lucia (Reports on Progress in Physics)
For the calculation of neutral excitations, time-dependent density functional theory (TDDFT) is an exact reformulation of the many-body time-dependent Schrödinger equation, based on knowledge of the density instead of the many-body wavefunction. The density can be determined in an efficient scheme by solving one-particle non-interacting Schrödinger equations—the Kohn–Sham equations. The complication of the problem is hidden in the—unknown—time-dependent exchange and correlation potential that appears in the Kohn–Sham equations and for which it is essential to find good approximations. Many approximations have been suggested and tested for finite systems, where even the very simple adiabatic local-density approximation (ALDA) has often proved to be successful. In the case of solids, ALDA fails to reproduce optical absorption spectra, which are instead well described by solving the Bethe–Salpeter equation of many-body perturbation theory (MBPT). On the other hand, ALDA can lead to excellent results for loss functions (at vanishing and finite momentum transfer). In view of this and thanks to recent successful developments of improved linear-response kernels derived from MBPT, TDDFT is today considered a promising alternative to MBPT for the calculation of electronic spectra, even for solids. After reviewing the fundamentals of TDDFT within linear response, we discuss different approaches and a variety of applications to extended systems.

Ab initio study of the half-metal to metal transition in strained magnetite - Friák, Martin; Schindlmayr, Arno; Scheffler, Matthias (New Journal of Physics)
Using density-functional theory, we investigate the stability of the half-metallic ground state of magnetite under different strain conditions. The effects of volume relaxation and internal degrees of freedom are fully taken into account. For hydrostatic compression, planar strain in the (001) plane and uniaxial strain along the [001] direction, we derive quantitative limits beyond which magnetite becomes metallic. As a major new result, we identify the bond length between the octahedrally coordinated iron atoms and their neighbouring oxygen atoms as the main characteristic parameter, and we show that the transition occurs if external strain reduces this interatomic distance from 2.06 Å in equilibrium to below a critical value of 1.99 Å. Based on this criterion, we also argue that planar strain due to epitaxial growth does not lead to a metallic state for magnetite films grown on (111)-oriented substrates.

Quasiparticle calculations for point defects at semiconductor surfaces - Schindlmayr, Arno; Scheffler, Matthias (Theory of Defects in Semiconductors)
We present a quantitative parameter-free method for calculating defect states and charge-transition levels of point defects in semiconductors. It combines the strength of density-functional theory for ground-state total energies with quasiparticle corrections to the excitation spectrum obtained from many-body perturbation theory. The latter is implemented within the G0W0 approximation, in which the electronic self-energy is constructed non-self-consistently from the Green’s function of the underlying Kohn–Sham system. The method is general and applicable to arbitrary bulk or surface defects. As an example we consider anion vacancies at the (110) surfaces of III–V semiconductors. Relative to the Kohn–Sham eigenvalues in the local-density approximation, the quasiparticle corrections open the fundamental band gap and raise the position of defect states inside the gap. As a consequence, the charge-transition levels are also pushed to higher energies, leading to close agreement with the available experimental data.

On Testable Properties in Bounded Degree Graphs - Sohler, Christian; Czumaj, Artur (Proceedings of the 17th ACM-SIAM Symposium on Discrete Algorithms (SODA'07))
We study graph properties which are testable for bounded degree graphs in time independent of the input size. Our goal is to distinguish between graphs having a predetermined graph property and graphs that are far from every graph having that property. It is believed that almost all, even very simple graph properties require a large complexity to be tested for arbitrary (bounded degree) graphs. Therefore in this paper we focus our attention on testing graph properties for special classes of graphs. We call a graph family non-expanding if every graph in this family is not a weak expander (its expansion is O(1/log2 n), where n is the graph size). A graph family is hereditary if it is closed under vertex removal. Similarly, a graph property is hereditary if it is closed under vertex removal. Next, we call a graph property Π to be testable for a graph family F if for every graph G ε F, in time independent of the size of G we can distinguish between the case when G satisfies property Π and when it is far from every graph satisfying property Π. In this paper we prove thatIn the bounded degree graph model, any hereditary property is testable if the input graph belongs to a hereditary and non-expanding family of graphs.As an application, our result implies that, for example, any hereditary property (e.g., k-colorability, H-freeness, etc.) is testable in the bounded degree graph model for planar graphs, graphs with bounded genus, interval graphs, etc. No such results have been known before and prior to our work, in the bounded degree graph model very few graph properties have been known to be testable for any graph classes.

StrSort Algorithms for Geometric Problems - Sohler, Christian; Lammersen, Christiane (Proceedings of the 23rd European Workshop on Computational Geometry (EWCG))
In the StrSort model [2], the input is given as a stream, e.g. a sequence of points, and an algorithm can perform (a) streaming and (b) sorting passes to process the stream. A streaming pass reads the input stream from left to right and writes an output stream, which is the input of the next pass. A sorting pass is a black box operation that sorts a stream according to some partial order. In this paper, we develop algorithms for two basic geometric problems in the StrSort model. At first, we propose a divide-and-conquer algorithm that computes the convex hull of a point set in 2D in O(log2 n) passes using O(1) memory. Then we give a StrSort algorithm to compute a (1+ε)-spanner for a point set in Rd for constant d and constant epsilon that uses O(logd-1 n) passes and O(log n) space. This result implies a (1+ε)-approximation of the Euclidean minimum spanning tree in Rd, for constant d and ε.

Testing Expansion in Bounded-Degree Graphs - Sohler, Christian; Czumaj, Artur (Proceedings of the 48th Annual IEEE Symposium on Foundations of Computer Science (FOCS))

Small Space Representations for Metric Min-Sum k-Clustering and their Applications - Sohler, Christian; Czumaj, Artur (Proceedings of the 24th International Symposium on Theoretical Aspects of Computer Science (STACS'07))

Sublinear-time approximation algorithms for clustering via random sampling - Sohler, Christian; Czumaj, Artur (Random Structures & Algorithms)
We present a novel analysis of a random sampling approach for four clustering problems in metric spaces: k-median, k-means, min-sum k-clustering, and balanced k-median. For all these problems, we consider the following simple sampling scheme: select a small sample set of input points uniformly at random and then run some approximation algorithm on this sample set to compute an approximation of the best possible clustering of this set. Our main technical contribution is a significantly strengthened analysis of the approximation guarantee by this scheme for the clustering problems.The main motivation behind our analyses was to design sublinear-time algorithms for clustering problems. Our second contribution is the development of new approximation algorithms for the aforementioned clustering problems. Using our random sampling approach, we obtain for these problems the first time approximation algorithms that have running time independent of the input size, and depending on k and the diameter of the metric space only. © 2006 Wiley Periodicals, Inc. Random Struct. Alg., 2007A preliminary extended abstract of this work appeared in Proceedings of the 31st Annual International Colloquium on Automata, Languages and Programming (ICALP), pp. 396407, 2004.

A PTAS for k-means clustering based on weak coresets - Sohler, Christian; Monemizahdeh, Morteza; Feldman, Dan (Proceedings of the 23rd annual symposium on computational geometry (SoCG'07))

Efficient kinetic data structures for MaxCut - Sohler, Christian; Czumaj, Artur; Frahling, Gereon (Proceedings of the 19th Canadian Conference on Computational Geometry (CCCG))

Dynamic and redundant data placement - Brinkmann, André; Effert, Sascha; Meyer auf der Heide, Friedhelm; Scheideler, Christian (IEEE International Conference on Distributed Computing Systems (ICDCS))
We present a randomized block-level storage virtualization for arbitrary heterogeneous storage systems that can distribute data in a fair and redundant way and can adapt this distribution in an efficient way as storage devices enter or leave the system. More precisely, our virtualization strategies can distribute a set of data blocks among a set of storage devices of arbitrary non-uniform capacities so that a storage device representing x% of the capacity in the system will get x% of the data (as long as this is in principle possible) and the different copies of each data block are stored so that no two copies of a data block are located in the same device. Achieving these two properties is not easy, and no virtualization strategy has been presented so far that has been formally shown to satisfy fairness and redundancy while being time- and space-eflcient and allowing an efficient adaptation to a changing set of devices.

Von der Mechatronik zur Selbstoptimierung - Frank, Ursula; Gausemeier, Jürgen; Schmidt, Alexander; Zimmer, Detmar (Internationales Forum Mechatronik. Intelligente Systeme und Module)

Using Active Patterns for the Conceptual Design of Self-Optimizing Systems Exemplified by an Air Gap Adjustment System - Gausemeier, Jürgen; Dangelmaier, Wilhelm; Zimmer, Detmar; Schmidt, Alexander; Frank, Ursula; Klöpper, Benjamin (Computers and Information in Engineering Conference, Parts A and B)

Conceptual Design of Self-Optimizing Systems Exemplified by a Magnetic Linear Drive - Gausemeier, Jürgen; Zimmer, Detmar; Frank, Ursula; Pook, Sebastian; Schmidt, Alexander (International Conference of Engineering Design)

Messung von radialen Lagerkräften an einem CVT-Variator mit Schubgliederband - Zimmer, Detmar; Möller, Jens (VDI-Gesellschaft Entwicklung Konstruktion Vertrieb (VDI-EKV))

Messung der radialen Lagerkräfte eines CVT-Variators - Zimmer, Detmar; Felgenhauer, Benedikt; Möller, Jens (Konstruktion - Zeitschrift für Produktentwicklung und Ingenieur-Werkstoffe)

Konzipierung selbstoptimierender Systeme am Beispiel eines magnetischen Linearantriebs - Gausemeier, Jürgen; Frank, Ursula; Pook, Sebastian; Zimmer, Detmar; Schmidt, Alexander

Dimensioning and tolerancing in international comparison. Confrontation of standardisation works of GPS and GD&T - Denzer, Vera (CIRP Conference on Computer Aided Tolerancing. Specification and Verification for Assemblies)

Untersuchungen zur Verformung, zum Lauf des Umschlingungsmittels und zur Reibung in einem stufenlosen Umschlingungsgetriebe - Felgenhauer, Benedikt

Modelling and Identification of an All-Terrain Vehicle - Bruns, Torsten; Schäfer, Erika (International Journal of Vehicle Systems Modelling and Testing 2007)

RailCab - Ein Schienenverkehrssystem mit autonomen, Linearmotor getriebenen Einzelfahrzeugen - Henke, Christian; Rustemeier, Carsten; Schneider, Tobias; Böcker, Joachim; Trächtler, Ansgar (Internationaler ETG - Kongress 2007)

Self-Calibration of the 6-dof Parallel Robot TriPlanar by Identification of the Geometry Parameters - Cinkaya, Hueseyin; Noelle, Rene; Münch, Eckehard; Trächtler, Ansgar (AIM 2007)

X-by-Wire Test Vehicle for the Test of New Design Methods and Tools to Interconnect Vehicle-Dynamics Control Systems - Nachtigal, Vitalij; Trächtler, Ansgar; Jäker, Karl-Peter (5th IFAC Symposium on Advances in Automotive Control (AAC))

Optimal Control Inputs to Affect Vehicle Dynamics in Various Driving States - Salfeld, Maike; Stabrey, Stephan; Trächtler, Ansgar (5th IFAC Symposium on Advances in Automotive Control (AAC))

Modellierung des Papiertransports in Geldautomaten - Just, Viktor; Trächtler, Ansgar; Jäker, Karl-Peter (Mechatronik 2007)

Selbstkalibrierung des 6 DOF Parallelroboters TRIPLANAR durch Identifikation der Geometrieparameter mit einem einfachen Messverfahren - Cinkaya, Hueseyin; Münch, Eckehard; Noelle, Rene; Trächtler, Ansgar; Toepper, S. (Mechatronik 2007: Innovative Produktentwicklung)

Tool Support for Developing Advanced Mechatronic Systems: Integrating the Fujaba Real-Time Tool Suite with CAMeL-View - Burmester, Sven; Giese, Holger; Henkler, Stefan; Hirsch, Martin; Tichy, Matthias; Gambuzza, Alfonso; Münch, Eckehard; Voecking, Henner (29th International Conference on Software Engineering (ICSE))

Modellbasierter Entwurf mechatronischer Fahrwerksysteme - Trächtler, Ansgar (Paderborner Workshop Entwurf Mechatronischer Systeme (EMS))

Potenziale und Risiken der Selbstoptimierung für die Verlässlichkeit mechatronischer Systeme - Frank, Ursula; Giese, Holger; Müller, Thomas; Oberthür, Simon; Romaus, Christoph; Tichy, Matthias; Voecking, Henner (Paderborner Workshop Entwurf Mechatronischer Systeme (EMS))

Realisierung eines Werkzeuges zur algorithmischen Differenzierung von Modellen mechatronischer Systeme - Münch, Eckehard; Cinkaya, Hueseyin; Trächtler, Ansgar (Paderborner Workshop Entwurf Mechatronischer Systeme (EMS))

Analysis of the Vehicle Dynamics and Yaw Moment Maximization in Skid Maneuvers - Salfeld, Maike; Stabrey, Stephan; Trächtler, Ansgar (chassis.tech 2007)

Ein plattformunabhängiges Softwaretool für die schnelle Qualitätskontrolle von Transmissions- und dynamischen Emissionsdaten in der PET - Krevert, B.; Dang, T. B.; Weise, R.; Fricke, H.; Domik, Gitta; Buchert, W. (45. Jahrestagung der DGN)

Can ISPs and P2P users cooperate for improved performance? - Aggarwal, Vinay; Feldmann, Anja; Scheideler, Christian (ACM Computer Commucation Review)

Modellierung der Hysterese- und Adhäsionseffekte zwischen Bremsbelag und Bremsscheibe - Tonchev, Anton; Hirschberg, Wolfgang; Sextro, Walter; Major, Zoltan; Neges, Josef (27. Internationales Mju-Symposium/Bremsen-Fachtagung)

Modelling of Hysteresis and Adhesion Effects between Brake Pad and Disc - Tonchev, Anton; Hirschberg, Wolfgang; Sextro, Walter; Major, Zoltan; Neges, Josef (27. Internationales Mju-Symposium/Bremsen-Fachtagung)

Non-destructive ultrasonic test of orange dehydration - Camarena Gandia, Francisco; Hemsel, Tobias; Espinosa, Victor; Twiefel, Jens; Ardid, Miquel; Martinez-Mora, Joan; Gandia, Joan Babtiste (Proceedings of 19th international congress on Acoustics, Madrid)
Penetration tests (Magness-Taylor, force/deformation, Kramer multiblade shear) applied directly over the peel of the fruit are the most acceptable methods for measuring firmness and turgidity of fruits and vegetables [1, 2]. To replace these destructive and mechanical penetration methods by non-destructive ultrasonic measurements implies a great advance in order to obtain fast studies about the state of the fruit at the time of harvest, during storage, and in the distribution points. Moreover, there are other advantages since this technique can be fast, non-destructive, fully automated, and performed on-line [1]. Within this context, the objective of this study was to examine the relationship between physico-mechanical characteristics (oil-gland break stress, thickness and dehydration) and ultrasonic characteristics in the ``Salustiana'' orange peel during the complete dehydration process of the orange at ambient conditions. After a description of the measurement system [3], the fruit selection procedure and the measurement protocol, we analyze the results of the change of physico-mechanical and ultrasonic properties in the orange peel and their change with storage time.

Schwingungsverhalten elastischer Körper mit nichtlinearen Kopplungen in ausgedehnten Reibkontakten - Genzo, Alexander; Sextro, Walter; Panning, Lars (VDI-Berichte)

Resonant vibrating sensors for tactile tissue differentiation - Hemsel, Tobias; Stroop, Ralf; Oliva Uribe, David; Wallaschek, Jörg (Journal of Sound and Vibration)
Surgical resection of brain tumours is a difficult task. To enhance surgery results, a tactile sensor is wanted that gives better resolution and sensitivity than the human tactile sense. The characteristics of resonant vibrating piezoelectric elements change with varying load. This allows for calculation of mechanical load parameters by measuring electrical quantities. Different setups of piezoelectric sensors have been used to investigate soft materials. Finally, a piezoelectric bimorph sensor gave good results for distinguishing tissue mimicking gel-phantoms with different gelatine concentrations.

Perspectives of Tumour Therapy by Local Ultrasonic Hyperthermia and Thermal Ablation - Lierke, Ernst-Günter; Hemsel, Tobias (Proceedings of 19th international congress on Acoustics, Madrid)

Fundamental Study on A Thickness-Shear Transformer using X-Cut Lithium Niobate - Shigematsu , Takashi; Morita, Takeshi; Hemsel, Tobias (Proceedings of Symposium on Ultrasonic Electronics)

On Nonlinear Forced Vibration of Shrouded Turbine Blades - Szwedowicz, J; Visser, R; Sextro, Walter; Masserey, P. A (Journal of Turbomachinery)
Numerical predictions of the forced vibration of a disk assembly including frictional effects between the shrouds are presented concerning engineering needs for the blade design process. Assuming a tuned disk assembly, numerical static, free, and then forced vibration analyses of a shrouded turbine blade measured in the spin pit are performed systematically. For the excitation forces of an air jet evaluated from the fairly linear behavior of the experimental blade resonance peaks, the reliability of the proposed approach is validated through the very close agreement of the computed and measured resonant peaks. These resonant peaks demonstrate either a fairly linear behavior or a nonlinear one like the jump effect of blade resonance amplitudes, or elastic impacts between the shrouds. Also, the damping performance for different contact configurations between the shrouds is numerically analyzed. These numerical results indicate that the shrouds generate higher frictional damping for small angles (0â30deg) between the circumferential direction and the normal vector to the contact surface.

Proceedings of the 10th International Conference on Model Driven Engineering Languages and Systems (MoDELS 2007), Nashville, TN (USA)

Proceedings of the MoDELS 2007 Workshop on Model Driven Development of Advanced User Interfaces (MDDAUI '07), Nashville, Tennessee (USA)

A Model-Based Approach for Platform-Independent Binary Components with Precise Timing and Fine-Grained Concurrency - Schattkowsky, Tim; Engels, Gregor; Förster, Alexander (Proceedings of the 40th Annual Hawaii International Conference on System Sciences (HICSS 2007))

Generation of Business Process Models for Object Life Cycle Compliance - Küster, Jochen; Ryndina, Ksenia; Gall, Harald (Proceedings of the conference on Business Process Management (BPM 2007), Brisbane (Australia))

Model Driven Development of Advanced User Interfaces (MDDAUI) - MDDAUI'06 Workshop Report - Pleuß, Andreas; Van den Bergh, Jan; Sauer, Stefan; Hußmann, Heinrich; Bödcher, Alexander (MoDELS 2006 Workshops)

Easy Model-Driven Development of Multimedia User Interfaces with GuiBuilder - Sauer, Stefan; Engels, Gregor (Proceeding of the 4th International Conference on Universal Access in Human-Computer Interaction (UAHCI, as Part of HCI International, 2007), Beijing (China))
GUI builder tools are widely used in practice to develop the user interface of software systems. Typically they are visual programming tools that support direct-manipulative assembling of the user interface components. We have developed the tool GuiBuilder which follows a model-driven approach to the development of graphical (multimedia) user interfaces. This allows a meta-design approach where user interface developers as well as prospective users of the system are supported in modelling the desired functionality of the GUI on a high level of abstraction that is easy to understand for all involved stakeholders. The model consists of compositional presentation diagrams to model the structure of the user interface and hierarchical statechart diagrams to model its behaviour. GuiBuilder then supports the transformation of the model to Java, i.e., the generation of a working user interface and the simulation of the modelled behaviour. Interactive sessions with the user interface can be recorded and replayed.

ClassSheets - model-based, object-oriented design of spreadsheet applications - Bals, Jan-Christopher; Christ, Fabian; Engels, Gregor; Erwig, Martin (Proceedings of the TOOLS Europe Conference (TOOLS 2007), Zürich (Swiss))

KnowledgeBus - An Architecture to Support Intelligent and Flexible Knowledge Management - Mlynarski, Michael; Hinkelmann, Knut; Magenheim, Johannes; Nelkner, Tobias; Reinhardt, Wolfgang; Holzweissig, Kai (Creating New Learning Experiences on a Global Scale, Second European Conference on Technology Enhanced Learning, EC-TEL 2007, Crete, Greece, September 17-20, 2007)

Verification of Business Process Quality Constraints Based on Visual Process Patterns - Förster, Alexander; Engels, Gregor; Schattkowsky, Tim; Van Der Straeten, Ragnhild (Proceedings of the First Joint IEEE/IFIP Symposium on Theoretical Aspects of Software Engineering (TASE 2007), Shanghai (China))

Structuring Software Cities - A Multidimensional Approach - Hess, Andreas; Humm, Bernhard; Voß, Markus; Engels, Gregor (Proceedings of the 11th IEEE International Enterprise Distributed Object Computing Conference (EDOC 2007))

Vom Informations- zum Wissensmanagement: Der Knowledge Bus als flexibler Lösungsansatz - Mlynarski, Michael; Nelkner, Tobias; Reinhardt, Wolfgang (Informatiktage 2007: Fachwissenschaftlicher Informatik-Kongress, 30. und 31. März 2007, B-IT Bonn-Aachen International Center for Information Technology Bonn)

Improving Inconsistency Resolution with Side-effect Evaluation and Costs - Küster, Jochen; Ryndina, Ksenia; Gall, Harald (Proceedings of the ACM/IEEE 10th International Conference on Model Driven Engineering Languages and Systems (MODELS 2007), Nashville, TN (USA))

Generation of Business Process Models for Object Life Cycle Compliance - Ryndina, Ksenia; Küster, Jochen; Gall, Harald (Proceedings of the BPM Demonstration Program (satellite event of the 5th International Conference on Business Process Management (BPM 2007)), Brisbane (Australia))

Smart Teams: Simulating Large Robotic Swarms in Vast Environments - Arens, Stephan; Buss, Alexander; Deck, Helena; Dynia, Miroslaw; Fischer, Matthias; Hagedorn, Holger; Isaak, Peter; Kutylowski, Jaroslaw; Meyer auf der Heide, Friedhelm; Nesterow, Viktor; Ogiermann, Adrian; Stobbe, Boris; et al. (Proceedings of the 4th International Symposium on Autonomous Minirobots for Research and Edutainment)
We consider the problem of exploring an unknown environment using a swarm of autonomous robots with collective behavior emerging from their local rules. Each robot has only a very restricted view on the environment which makes cooperation difficult. We introduce a software system which is capable of simulating a large number of such robots (e.g. 1000) on highly complex terrains with millions of obstacles. Its main purpose is to easily integrate and evaluate any kind of algorithm for controlling the robot behavior. The simulation may be observed in real-time via a visualization that displays both the individual and the collective progress of the robots. We present the system design, its main features and underlying concepts.

Reusable Architectural Decision Models for Enterprise Application Development - Zimmermann, Olaf; Gschwind, Thomas; Küster, Jochen; Leymann, Frank; Schuster, Nelly (Proceedings the conference on Quality of Software-Architectures (QoSA 2007), Medford, MA (USA))

"Modelchecking" - Eine Methode zur Verbesserung der Softwarequalität - Gehrke, Matthias; Güldali, Baris; Kindler, Ekkart

Investigation of multicast-based mobility support in all-IP cellular networks - Festag, Andreas; Karl, Holger; Wolisz, Adam (Wireless Communications and Mobile Computing)

WASP - Wirelessly Accessible Sensor Populations: A Project Overview - van der Stok, Peter; Karl, Holger; De Ambroggi, Fabio; Decotignie, JeanDominique; Siegemund, Frank; Lokhorst, Kees; Hellenschmidt, Michael (Constructing Ambient Intelligence - AmI 2007 Workshops Darmstadt, Germany, November 7-10, 2007 Revised Papers)

Outage probability analysis of cooperative transmission protocols without and with network coding: inter-user channels based comparison - H. Woldegebreal, Dereje; Valentin, Stefan; Karl, Holger (Proceedings of the 10th International Symposium on Modeling Analysis and Simulation of Wireless and Mobile Systems, MSWiM 2007, Chania, Crete Island, Greece, October 22-26, 2007)

Traffic-Aware Asymmetric Cooperation Diversity for Media Streaming in Wireless Networks - Valentin, Stefan; von Malm, Holger; Karl, Holger (Proceedings of the IEEE 18th International Symposium on Personal, Indoor and Mobile Radio Communications, PIMRC 2007, 3-7 September 2007, Athens, Greece)

Integrating multiuser dynamic OFDMA into IEEE 802.11a and prototyping it on a real-time software-defined radio testbed - S. Lichte, Hermann; Valentin, Stefan; Eitzen, Falk; Stege, Matthias; Unger, Carsten; Karl, Holger (3rd International ICST Conference on Testbeds and Research Infrastructures for the Development of Networks and Communities, TridentCom 2007, Orlando, Florida, USA, May 21-23 2007)

Finanzwirtschaftliche Analyse der schenkungsteuerlichen Zehnjahresregel - Kundisch, Dennis; Pfeiler, F.; Schiefele, V. (Steuer und Wirtschaft)

MuPAD: eine Einführung - Rapin, Gerd; Wassong, Thomas; Wiedmann, Stefan; Koospal, Stefan
Keywords: mupad

Graphentheoretische Konzepte in der Gymnasialen Oberstufe: Ein Unterrichtsentwurf unter Berücksichtigung der Neuen Medien - Wassong, Thomas

Customer Portfolio Management in E-Commerce – A Risk Management Perspective - Kundisch, Dennis; Sackmann, S.; Ruch, M. (INFORMS International Puerto Rico 2007 Meeting)

Außerbörslicher Emittentenhandel: Handelsplatzwahl von Online-Investoren - Kundisch, Dennis; Stuber, T. (Wirtschaftsinformatik 2007 - eOrganisation: Service-, Prozess-, Market-Engineering)

Bank controlling using Basel II-data: Are internal approaches dispensable? - Kundisch, Dennis; Loehner, F.; Rudolph, D.; Steudner, M.; Weiss, C. (2007 Enterprise Risk Management Symposium Monograph)

Spezifizierung des Kano-Modells zur Messung von Kundenzufriedenheit - Buhl, H. U.; Kundisch, Dennis; Schackmann, N.; Renz, A. (Wirtschaftsinformatik 2007 - eOrganisation: Service-, Prozess-, Market-Engineering)

Feedbackgespräche: Überstrapaziert, missverstanden und bedeutungslos? Ganz im Gegenteil: Best Practise bei der Deutschen Bahn - Terlinde, P; Giardini, A; Kabst, Rüdiger; Halbach, J; Pelchrzim, H

Strategische Personalentwicklung: Wenn dem Bildungscontroller die Ziele fehlen - Giardini, A; Kabst, Rüdiger

Funktionale Äquivalente zur Personalplanung : Eine empirische Studie zur Personalplanung klein- und mittelständischer Unternehmen auf Basis des Cranet - Matiaske, W; Holtmann, D; Kabst, Rüdiger (Planung in kleinen und mittleren Unternehmen, Jahrbuch der KMU-Forschung und -Praxis 2007)

Leistungsbeurteilung und -vergütung in der privaten Wirtschaft und im öffentlichen Dienst: Eine vergleichende Betrachtung auf Basis des „Cranfield-Projects“ 1995-2005 - Giardini, A; Kabst, Rüdiger (Leistungsvergütung im Öffentlichen Dienst)

Preventing E-mail Spam: The Conceptualization and the Analysis of an Infrastructure Framework - Schryen, Guido
Spamming remains a form of Internet abuse, which burdens the Internet infrastructure, is generally regarded as an annoyance, and is said to cause a huge economic harm. Many technological, organizational, and legislative anti-spam measures have already been proposed and implemented, but have not led to any substantial decrease in the number of spam e-mails. We propose a scalable and flexible infrastructure framework that integrates several anti-spam measures and that features both a technological and an organizational facet. The key element of our infrastructure is a new organizational unit that reliably and transparently limits the number of e-mails that can be sent per day and per account. We also analyze the proposed framework in terms of its theoretical effectiveness, the required resources, and its limitations.
Keywords: Email; Infrastructure; Internet; Spam

Joint Venture Performance: A Meta-Analysis - Isidor, R; Hornung, F; Kabst, Rüdiger

Pre-and post entry learning of young technology firms: antecedents of objective and tacit knowledge and performance implications - Schwens, C; Kabst, Rüdiger

Self-Organization in Sensor and Actor Networks - Dressler, Falko
Self-organization is a rather fascinating concept that enables systems consisting of huge numbers of autonomously acting subsystems to perform a collective task. Moreover, self- organizing systems show an overall behavior that cannot easily be predicted or even preprogrammed in a scalable way. It was in the early 1960ies that people like Ashby and Eigen investigated self-organization properties in (natural) systems. Since these days, a great number of (technical) solutions have been developed, which, either on purpose or unintentionally, inherently the basic concepts of self-organization. The aim of this book is to investigate the concepts of self-organization in the context of autonomous sensor and actor networks. The primary objective is to categorize the basic self-organization methods and to survey techniques for communication and coordination in massively distributed systems according to the developed classification scheme. Basically, two possible approaches can be thought of for organizing this book. First, we could start analyzing sensor and actor network technology and figure out what basic mechanisms are employed and how these relate to self-organization. A second approach would be to introduce self-organization as a methodology, apparently used everywhere in our life (in nature and in technical systems), and afterwards to continue with technical issues in sensor and actor networks searching for previously learned self-organization methods. I decided to follow the second approach in order to keep the focus on self-organization while studying the term in the world of sensor and actor networks. The term self-organization is still often misunderstood and misinterpreted. Therefore, this textbook is intended to be a basis for a better understanding of the concepts of self-organization, especially in the domain of sensor and actor networks. It provides a stepwise introduction of definitions, methodologies, and corresponding techniques relevant in the context of self-organization. Recent advances in miniaturization and wireless communication enabled the development of low-cost sensor nodes. Additionally, new application domains of sensor and actor networks emerged that demand for huge numbers of interacting devices. Thus, the relevance of self-organization methods is rapidly increasing as it is considered the primary control paradigm for distributed and massively distributed systems. The reader will see that self-organization has a number of advantages compared to other control paradigms. So, it becomes possible to operate huge numbers of collaborating subsystems even in case of limited resources, unreliable communication, and in case of massive failures of single systems. Unfortunately, these advantages are accompanied by some rather annoying side effects such as the increasing complexity and a nondeterministic behavior. By using optimal combinations of the basic methods of self-organization, these disadvantages can be minimized to some extent. According to the objective of this textbook - to study sensor and actor networks - the most relevant domains of communication and coordination are deeply investigated based on well-known algorithms and mechanisms and a number of case studies. This includes networking aspects of medium access control, ad hoc routing, data-centric communication, and clustering techniques. Additionally, control mechanisms for cooperation, task and resource allocation, and collaborative actuation are investigated. The book is concluded by a brief introduction of the domain of bio-inspired algorithms. This study is included for two reasons. First, to demystify the term bio-inspired networking, and secondly, to show the capabilities of such bio-inspired approaches.

Einsatz von E-Portfolios zur Förderung von studentischen Lerngemeinschaften im Hochschulstudium. - Sporer, Thomas; Jenert, Tobias; Strehl, Bernhard; Noack, Patrick Ole (DeLFI Workshops)
Keywords: E-Portfolios; Lerngemeinschaften; Praxisgemeinschaften; Projektgruppen; Hochschulstudium; informelles Lernen

Learning about innovation and knowledge creation in higher education. - Sporer, Thomas; Jenert, Tobias; Reinmann, Gabi (4. Konferenz Professionelles Wissensmanagement - Erfahrungen und Visionen)

Semivirtuelle Lernumgebung zum wissenschaftlichen Arbeiten als Ergänzung des Studienangebots der Universität Augsburg - Heinze, Nina; Sporer, Thomas; Jenert, Tobias (Deutsche Gesellschaft für Informationswissenschaft und Informationspraxis: Tagungen der Deutschen Gesellschaft für Informationswissenschaft und Informationspraxis)
Keywords: Wissenschaftliches Arbeiten; Blended Learning; Tutoring

Student Learning Communities in the Project-Centered Study Program" Problem-Solving Competencies" - Sporer, Thomas; Heinze, Nina; Jenert, Tobias; Reinmann, Gabi
Keywords: Problem Solving Competencies; E-Portfolio

Begleitstudium Problemlösekompetenz (Version 2.0). Infrastruktur für studentische Projekte an Hochschulen - Sporer, Thomas; Reinmann, Gabi; Jenert, Tobias; Hofhues, Sandra (Studieren neu erfinden - Hochschule neu denken)

Fallstudie: Social Software im Hochschulstudium - Sporer, Thomas; Jenert, Tobias (Enterprise 2.0 - Planung, Einführung und erfolgreicher Einsatz von Social Software im Unternehmen)

p-Shell Rabi-flopping and single photon emission in an InGaAs/GaAs quantum dot - Ester, P.; Lackmann, L.; Hübner, M.C.; Michaelis de Vasconcellos, S.; Zrenner, Artur; Bichler, M. (Physica E: Low-dimensional Systems and Nanostructures)
Very clean single photon emission from a single InGaAs/GaAs quantum dot is demonstrated by the use of a coherent optical state preparation. We present a concept for single photon emission, which uses p-shell Rabi-flopping followed by a sequence of relaxation and recombination. The proof of the (clean) single photon emission is performed by photon correlation measurements.
Keywords: Antibunching; Single photon emission; Rabi oscillation; Coherent manipulation

On the asymptotic variance in nonparametric regression with fractional time-series errors - Feng, Yuanhua (Journal of Nonparametric Statistics)

Modelling financial time series with SEMIFAR GARCH model - Feng, Yuanhua; Beran, J.; Yu, K. (IMA Journal of Management Mathematics)

Semiparametric Modeling of Stochastic and Deterministic Trends and Fractional Stationarity - Beran, Jan; Feng, Yuanhua; Franke, Günter; Hess, Dieter; Ocker, Dirk (Processes with Long-Range Correlations)

Local Polynomial Estimation with a FARIMA-GARCH Error Process - Beran, Jan; Feng, Yuanhua (Bernoulli)

Special Issue: Quantile Regression

Kundenbindung durch Weiterempfehlung? Eine experimentelle Untersuchung der Wirkung positiver Kundenempfehlungen auf die Bindung des Empfehlenden. - Eggert, Andreas; Helm, Sabrina; Garnefeld, Ina (Marketing ZfP)

Immigration policy and the labor market: the German experience and lessons for Europe - Zimmermann, Klaus F; Bonin, Holger; Fahr, Rene; Hinte, Holger

On the inverse relationship between unemployment and absenteeism: evidence from natural experiments and worker heterogeneity - Fahr, Rene; Frick, Bernd